MICROWAVE-ASSISTED EXTRACTION OF INULIN FROM JERUSALEM ARTICHOKE AND PARTIAL ACID HYDROLYSES - & Abood, Alabadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The Recent study aimed to identify the optimum conditions for inulin extraction from jerusalem artichoke tuber (JAT) powder using microwave assisted extraction method, and partially hydrolysis of purified inulin for producing fructooligosaccharide (FOS) using citric acid & microwave energy. The extraction conducted at different temperature (90 – 95) C˚ at (700 W/5min, 450w/8 min and 350w/14 min). The extracted inulin was concentrated to (50 – 60) % of original volume using rotary evaporator, and purified by lime method. The purified inulin extract was concentrated to 32 brix and mixed with acetone (3:1 acetone : extract), kept for 24 h at 4 C˚, then centrifuged at 10000g / 15 min., the precipitate dried at 55 ˚C. Acid hydrolysis of purified inulin carried out at different pH values (1.5, 2.5 & 3.0) at (90 ±2) ˚C. Aliquot of inulin hydrolysate were taken after (5, 10, 15, 20, 25 & 30) min. and subjected to qualitative analysis by RP-HPLC and TLC. The obtained results indicated that the microwave assisted extraction at 700 W/ 5 min. / 95 ˚C was superior as compared to the rest. The yield of extracted inulin was about 39.61 % and the extraction efficiency was 94.31 %, while the optimum condition for inulin acid hydrolysis appeared to be at 90 ˚C/ 15 min at pH 2.5 and 450 W. The qualitative analysis using (RP-HPLC & TLC) showed that the DP of inulin units ranged from (2 - 35) and for FOS ranged from (2 – 9) unit.